KONTRIBUSI TRADISI HAROA DALAM PENDIDIKAN KARAKTER MASYARAKAT BUTON - Nurdin Karim (Institut Agama Islam Negeri Kendari, 2017)
This study aims to (1) find out how the harmonic tradition exists in Buton society, (2) know the tradition forms of Buton society, and (3) know the character values in the tradition of Buton society. This study uses a descriptive qualitative approach that describes the process of harmonic tradition implementation in Buton society. The data is obtained through observation, interview, and documentation. The data source consists of 15 people consisting of syara Masjid, customary leaders, and village and community leaders. Data analysis is undertaken by using Miles & Huberman analysis model. The results showed that the implementation of the haroa is a hereditary tradition created by Buton society where the implementation is done from house to house, in the mosque, and in other places mutually agreed. The forms of haroa practice can be classified as follows: (a) haroa for the big days of Islam, such as isra'mi'raj, maulid of the Prophet Mauhammad Saw, Sha'ban, ramadhan, lailatul qadar night, feast of Eid fithri and Eid adha (b) haroa for syukuran / selamatan, (c) haroa for death (poalona mate). The character values contained in the tradition of the haroa are religiousity, gratitude, togetherness, love and affection, unity, help, care, deliberation, and tolerance.